MACROECONOMIC FOUNDATIONS OF THE TRANSITION TO A GREEN ECONOMY: IN-DEPTH ANALYSIS AND STRATEGIC OUTCOMES (Лучшие интеллектуальные исследования, 2025)
Abstract. This article provides an in-depth analysis of the macroeconomic foundations and strategic implications of transitioning to a green economy. Drawing on two decades of economic research, it argues that a green economy, defined as fostering economic growth while significantly reducing environmental risks and ecological scarcities, is crucial for addressing global challenges like climate change and resource depletion. The paper comprehensively examines the pivotal roles of macroeconomic policies, including fiscal (green taxes, subsidies), monetary (green finance, climate risk integration), and trade policies (technology transfer), in steering this transformation. It delves into the diverse economic outcomes, such as fostering innovation, creating new green jobs, enhancing resource efficiency, reducing energy dependence, and improving social well-being. Furthermore, the analysis addresses key implementation challenges, including high upfront investment costs, impacts on traditional industries, and the need for strong political will and institutional capacity. Special attention is given to sectoral nuances in energy, agriculture, industry, and urban development, emphasizing the imperative of social equity and "Just Transition" mechanisms. The article concludes by highlighting the indispensable role of international cooperation, particularly for developing countries and regions like Central Asia, in mobilizing finance, facilitating technology transfer, and addressing transboundary environmental issues, ultimately paving the way for sustainable and inclusive global prosperity.